2017
DOI: 10.1007/s11096-017-0574-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal pharmacists’ perceptions and current practices of assessing medication adherence in dialysis patients

Abstract: Perception scores, scale reliability, and responses to current practices questionnaire. Results 41 pharmacists completed the survey (response rate, 91.1%). The majority (91.9%, n = 34; median = 8.0) agreed patients were nonadherent to medication. Time constraints (43.8%, n = 14) and hospital support (31.3%, n = 10) were perceived as barriers to assessment. Objective blood monitoring was frequently used to determine nonadherence (57.1%, n = 16), whereas subjective interviews were rarely conducted (27.6%, n = 8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…We observed that current adherence assessment practices are limited and that the methods used to monitor nonadherence behaviour, such as medication history taking, and medication reviews and reconciliation by pharmacists, were only occasionally conducted, whereas objective blood monitoring was a routine practice in most settings. A recent survey on renal pharmacists’ perceptions corroborated the study's findings on current adherence assessment practices in dialysis settings (Ghimire et al., ). Objective blood monitoring in patients undergoing dialysis is mainly conducted to ensure that the dialysis prescription, that is, the time and type of the dialysis treatments, is optimal.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We observed that current adherence assessment practices are limited and that the methods used to monitor nonadherence behaviour, such as medication history taking, and medication reviews and reconciliation by pharmacists, were only occasionally conducted, whereas objective blood monitoring was a routine practice in most settings. A recent survey on renal pharmacists’ perceptions corroborated the study's findings on current adherence assessment practices in dialysis settings (Ghimire et al., ). Objective blood monitoring in patients undergoing dialysis is mainly conducted to ensure that the dialysis prescription, that is, the time and type of the dialysis treatments, is optimal.…”
Section: Discussionsupporting
confidence: 61%
“…During the thorough literature search, we could not identify any validated tools that particularly measured dialysis nurses’ perceptions regarding adherence assessment practices. Hence, we adapted a previously developed survey instrument that measured renal pharmacists’ perceptions and practices of assessing adherence in dialysis settings (Ghimire, Banks, Jose, Castelino, & Zaidi, ). To briefly describe the instrument, it comprised seven sections that explored demographics, perceptions of the prevalence of, and contributors to nonadherence, the perceived effectiveness of methods used to detect nonadherence, barriers to adherence assessment and participants’ confidence in assessing adherence.…”
Section: Methodsmentioning
confidence: 99%
“…However, these are often less explored aspects of patient adherence reported in medical literatures. In two separate surveys (Ghimire, Banks, Jose, Castelino, & Zaidi, 2017, renal nurses and pharmacists reported time constraints , lack of support from hospital administration , and patient's unwillingness to discuss medication-related issues with nurses (Ghimire et al, 2018) as potential barriers to assessing adherence during routine care.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of HCPs' practice for assessing adherence in hemodialysis settings primarily recruited nurses and pharmacists' [6][7][8]. The studies by Ghimire et al describe that time restraints and shortage of resource combined with insufficient training and lack of awareness challenge adherence assessment in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The studies by Ghimire et al describe that time restraints and shortage of resource combined with insufficient training and lack of awareness challenge adherence assessment in Australia. Multidisciplinary support from pharmacists, nurses and physicians working together with active patient involvement is recommended to improving patient adherence to treatment [6][7][8]. Gilad et al interviewed physicians, nurses and patients about their attitudes and approaches to medical care in a dialysis setting in Israel [9].…”
Section: Introductionmentioning
confidence: 99%